(3GOGQI GdYedjGJ (B/s - (3TGajQ, SchJs; (3LGc, ejQOjKs ((3GdQjGV(B: s (3OGQ GdeQjN(B, s, 2005)
(3GdYedjGJ aj GdShb GdYGdej(B-(3JUeje GdefJL hfXGe GdJMhjd(B-(3YedjGJ EOGQI GdehGQO(B-(3YedjGJ JhQjO GdefJLs
Keywords: (3EOGQI GdLhOIs; (3EOGQI GdeNRhfs; (3EOGQI GdeTQhYs; (3GdJfHDs; (3GdYedjGJ s; (3fXGe GdJMhjds